Influence of washing parameters on biomass and biochar properties of empty fruit bunches from oil palm plantation - Suriani binti Abu Bakar (Tanjung Malim, 2024)
Influence of washing parameters on biomass and biochar properties of empty fruit bunches from oil palm plantation by Suriani binti Abu Bakar